Studies Towards the Total Synthesis of Illicium Derived Neolignans - Giangone, Salvatore (2023)
Illicium derived neolignans are a class of structurally diverse secondary metabolites which arise in nature from the chemical manipulation of chavicol units. There is a growing interest in Illicium derived neolignans as they have been shown to provide neuroprotective effects. Recent studies have shown that neolignans can facilitate the growth and protection of developing neurons.